Impact of Timing the Combination of Radiotherapy and PD-1 Inhibitors on Outcomes in Patients with Hepatocellular Carcinoma - Zhong L; Peng W; Sun J; Luo Y; Sheng H; Wu Y; Zhou T; Zhou C; Cao C (Journal of Hepatocellular Carcinoma)
Liting Zhong,1,2,* Weiwei Peng,1,2,* Jingyuan Sun,3 Yongyi Luo,3 Hailong Sheng,4 Yi Wu,5 Tonggang Zhou,5 Chaoming Zhou,1,2 Chuanhui Cao1,3 1Department of Oncology, Ganzhou Hospital-Nanfang Hospital, Southern Medical University, Ganzhou, Jiangxi, People’s Republic of China; 2Department of Oncology, Ganzhou People’s Hospital, Ganzhou, Jiangxi, People’s Republic of China; 3Department of Radiation Oncology, Nanfang Hospital, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 4Department of Radiation Oncology, Zhejiang Provincial People’s Hospital, People’s Hospital of Hangzhou Medical College, Hangzhou, Zhejiang, People’s Republic of China; 5Department of Interventional Radiology, Ganzhou People’s Hospital, Ganzhou, Jiangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chuanhui Cao, Department of Oncology, Ganzhou Hospital-Nanfang Hospital, Southern Medical University, No. 16 Meiguan Avenue, Ganzhou, Jiangxi, People’s Republic of China, Email huichuancao@163.comPurpose: The optimal timing for combining radiotherapy with immunotherapy in patients with hepatocellular carcinoma (HCC) remains uncertain and affects treatment efficacy and patient outcomes. This study aimed to evaluate and compare the efficacy and treatment-related adverse events (TRAEs) of synchronously administered radiotherapy and programmed cell death protein (PD)-1 inhibitors and sequential administration in patients with HCC.Patients and Methods: We retrospectively enrolled 67 patients with HCC who were undergoing liver radiotherapy and PD-1 inhibitor therapy at two medical centers between July 2017 and April 2023. Additionally, we created an experimental tumor model using 6-week-old female mice to validate our findings.Results: In the concurrent group, the median overall survival was indefinite; however, it was 13 months in the sequential group (95% confidence interval [CI] 6.7– 19.3 months, P=0.010). The median progression-free survival was significantly longer in the concurrent group (12 months, 95% CI 9.5– 14.5 months) than in the sequential group (7 months, 95% CI 1.3– 12.7 months; P=0.043). Grade 3/4 TRAEs occurred in 30.4% (concurrent) and 28.6% (sequential) of patients without any treatment-related deaths. In the mouse model, synchronous treatment significantly inhibited tumor growth compared to sequential treatment (293.4± 45.18 mm3 versus 602.7± 41.68 mm3; P=0.001). Flow cytometry revealed an increased Tregs/CD3+ T cell ratio and a decreased CD8+/Treg cell ratio post-radiotherapy, suggesting an immunosuppressive tumor microenvironment.Conclusion: Synchronous treatment demonstrated superior efficacy in treating HCC compared to sequential treatment, with manageable adverse events. The rapid increase in Tregs after radiotherapy may contribute to the reduced efficacy of sequential radiotherapy plus PD-1 inhibitors.Keywords: immunotherapy, treatment efficacy, adverse events, tumor microenvironment